Schools as a platform for promotion and scaling of agrobiodiversity conservation for better nutrition - Anunciado, Ma. Shiela; Del Rio, Susan; Tamondong, Shanerisse; Umali, Diana Jean; Monville-Oro, Emilita; Gonsalves, Julian; Hunter, Danny; Borelli, Teresa; Mendonce, Sharon (2023)
Agrobiodiversity conservation is an important aspect of sustainable agriculture and food and nutrition security; and schools can play a major role in promoting agrobiodiversity conservation among students and the wider community. The International Institute of Rural Reconstruction in collaboration with the Department of Science and Technology – Food and Nutrition Research Institute and, the Department of Education developed the Integrated School Nutrition Model in the Philippines with support from Canada’s International Development Research Center in 2016. This involved the establishment of a network of Lighthouse Schools and school-based Crop Museums (which are located within the network of LSs).